Inclusive Education Reform In Mentawai Islands Cooperation for Teachers - Irdamurni Irdamurni; Mega Iswari; Asep A Sopandi; Johandri Taufan; Yarmis Hasan (Universitas Negeri Padang, 2020)
Reforms on inclusive education began to be carried out in Tua Pejat area, North Sipora District, Mentawai Islands by conducting training on the implementation of inclusive education by Padang State University lecturers in the context of carrying out community service for special education lecturers, followed by elementary school teachers from six elementary schools and special school teachers from two special schools in the North Sipora sub-district of the Mentawai islands. The training was conducted with a question and answer lecture method, accompanied by a demonstration simulation method and assignments on developing a learning plan (RPP) in an inclusive class, namely modified lesson plans and modified lesson plans adapted to the characteristics and learning needs of children with special needs in the classroom. The results of the training show that collaboration between elementary and high school teachers is established, both by collaborating and cooperating in serving children with special needs in primary schools, where ing to assist elementary school teachers in matters related to the identification and assessment of children with special needs in inclusive schools, as well as working together in developing lesson plans and PPI for children with special needs in inclusive classes, and learning strategies in inclusive settings.